Efecto de la aplicación de bioabono en el rendimiento de cultivos de Vigna - Flores Blandón, Nelson Roberto (Agronomía Mesoamericana, 2016)
Organic materials as a soil amendment may be chellply prod used in farmer' s fields via anaerobic digestion of beef manure. From the anaerobic digestion, one obtains gas and manure, the latter having excellent physical and chemical properties which makes it a good source of organic matter. The objectives of this work were to evaluate the effects of beef manure applications on Vigna (Vigna unguiculata) yields Experiments were conducted for two years at the National School of Agriculture, El Salvador, 460 meters aoove sea level, 1800 mm annual precipitation,and a mean temperature of 23.8°C. The soil in this study was an alluvial saody loam Regosol.A total of five treatments were evaluated that included three rates of applied beef manure (40,80, 120 m3/ha), an inorganic fertilizer check (0.39 aud 0.20 kg/20 m2 of ammonium sulfate and urea respectively) and an absolute check (no N applied). The beef manure was applied to the soil eightdays before planting. The urea fraction of the inorganic fertilizer check was banded 8 days after planting. Fresh weight yields were statistically similar between manure and the inorganic fertilizer check in the tirst year, however, a slight tendency for higher yields was observed for the second year. This suggests that applications of manure can improve Vigna fresh weight yields over time.